Hybrid photoanodes for visible light-driven water oxidation: the beneficial and detrimental effects of nickel oxide cocatalyst. (27th August 2020) - Longchin, Pimchanok; Mitoraj, Dariusz; Reyes, Oliver Mendoza; Adler, Christiane; Wetchakun, Natda; Beranek, Radim
Abstract: Hybrid photoanodes comprising polymer-based light absorbers coupled to oxygen-evolving cocatalysts represent a promising, yes still underdeveloped, approach to photoelectrochemical splitting of water into hydrogen and oxygen. In this study, we investigate nickel oxide (NiO x ) nanoparticles as a water oxidation catalyst in hybrid photoanodes based on polymeric carbon nitride (CN x ) supported on electron-collecting mesoporous TiO2 support. The performance of the resulting TiO2 –CN x /NiO x photoanodes is evaluated with respect to our previous results on hybrid TiO2 –CN x photoanodes modified with IrO x and CoO(OH) x cocatalysts. The deposition of NiO x into TiO2 –CN x photoanodes enhances significantly the photocurrent (from <8 μ A to >250 μ A cm –2 at 1.23 V vs. RHE) under visible light irradiation ( λ > 420 nm, ∼200 mW cm −2 ) and triggers the photoelectrocatalytic oxygen evolution. No oxygen evolution was observed without a cocatalyst. As compared to photoanodes modified with IrO x or CoO(OH) x, the TiO2 –CN x /NiO x photoanodes excel by the very negative photocurrent onset potential (0 V vs . RHE), which we ascribe to good hole-extracting properties of NiO x . However, the comparatively low Faradaic efficiencies for oxygen evolution (∼18%) and dramatically decreased operational stability of the photoanodes indicate that the extracted holes do not efficiently oxidize water to dioxygen, but instead accumulate in the NiO x particles and increase thus the oxidative photodegradation of the photoanodes. Our study highlights the fact that employing outstanding electrocatalysts like NiO x in photoelectrochemical water-splitting systems does not necessarily lead to satisfactory results, especially when the photoelectrode cannot be operated at optimal pH due to light absorber stability issues.